Effects of feed formula and farming system on the environmental performance of shrimp production chain from a life cycle perspective. (20th December 2022) - Al Eissa, Ahmad; Chen, Peng; Brown, Paul B.; Huang, Jen‐Yi
Abstract: Shrimp is the most popular seafood in the United States; its production plays an important role in the aquaculture industry. However, shrimp farming causes various environment impacts that must be mitigated to ensure the sustainability of shrimp production. This study performed a life cycle assessment (LCA) on two US‐based and one Vietnam‐based shrimp production chains from cradle to US market covering three farming systems and eight shrimp feed formulae. Midpoint environmental impacts including terrestrial acidification, freshwater eutrophication, and global warming were determined. For the intensive production chain (IPC), feed production was identified as the main contributor to the terrestrial acidification potential (TAP) and global warming potential (GWP), and its freshwater eutrophication potential (FEP) was dominated by shrimp farming. Poultry by‐product and fish meals were the feed ingredients contributing high TAP and GWP. However, soybean, wheat, and corn gluten meals produced higher FEP; hence, substituting plant‐based proteins for animal‐based ones in shrimp feeds did not all have positive environmental consequences. Shrimp farming was the hotspot of all the environmental impacts of the semi‐intensive production chain (SPC) and extensive production chain (EPC), except for the TAP of the EPC. Among the three production chains, the IPC had the highest FEP due to the on‐farm discharge of phosphorus‐containing wastewater, and the SPC caused the highest TAP because of the intensive uses of electricity and fertilizers for pond cultivation. Although the EPC was most sustainable in terms of TAP and FEP, open farming in mangrove areas produced the highest GWP owing to land transformation. This LCA study is expected to serve as US shrimp farmers' decision‐making guidelines to adapt farming practices with lower environmental footprint.